#### Answer

Centre = (-3, -3)
Radius = 2

#### Work Step by Step

$(x-h)^{2}$ + $(y-k)^{2}$ = $r^{2}$
Centre = (h, k)
Radius = r
$(x+3)^{2}$ + $(y+3)^{2}$ = $2^{2}$
Centre = (-3, -3)
Radius = 2

Published by
Pearson

ISBN 10:
0321726391

ISBN 13:
978-0-32172-639-1

Centre = (-3, -3)
Radius = 2

You can help us out by revising, improving and updating this answer.

Update this answerAfter you claim an answer you’ll have **24 hours** to send in a draft. An editor
will review the submission and either publish your submission or provide feedback.